Estudo da posturografia dinâmica - “Foam-Laser” - em indivíduos normais com idades entre 14 e 60 anos - Ruwer, Sheelen Larissa (2006)
The corporal balance is fundamental to that the individual keeps his quality of life and get to do his daily life activities. The maintenance of the balance depends on three systems: the vision, the proprioceptive system and the vestibular system. Being multiple the corporal balance alterations causes, its diagnosis, not rare, constitute a challenge for the physician and the patient. On this way, being the Dynamic Posturography recognized like the most global form to observe the balance alterations, it becomes an excellent resource. Thus, the present work has as objective to study the Dynamic Posturography using the "Foam-Laser Dynamic Posturography" technique in individuals of different genders and ages variyng between 14 and 60 years old, in order to assist in a more accurate diagnosis of the balance disturbances, allowing to characterize its type and intensity in accordance with each individual. 204 individuals had been evaluated without corporal balance alteration complaints, being 97 of the female gender and 107 of the male gender. The individuals had been submitted to the evaluation using the Dynamic Posturografia "Foam-Laser". The results statiscally demonstrate a significant difference in the Organization Sensorial Test (SOT) in function of the individuals gender and ages, the women had presented better values in the most part of the SOT, in the different ages. It can be concluded that it has the necessity of values differentiated for SOT of the Dynamic Posturografia "Foam-Laser" between men and women in agreement with the age group. As well as, the accomplishment of new studies, that objectified the standardization of the Dynamic Posturografia "Foam-Laser", in function of the individuals gender and ages